2016
DOI: 10.1108/ijse-04-2015-0079
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weather on the European stock market

Abstract: Purpose The purpose of this paper is to ascertain whether weather variables can explain the stock return reaction on the Dow Jones Sustainability Europe Index by employing a number of macroeconomic indicators as control variables. Design/methodology/approach The authors incorporate the generalized autogressive conditional heteroskeasticity model in methodology for the period August 26, 2009 to May 30, 2014 using daily data. Findings The empirical results indicate that not only do changes in humidity and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Exchange rate, forex reserve, current account balance and oil price effect selectively to these sectors. Sariannidis et al (2016) examined the reaction of stock market in Europe due to change in weather condition and found that it has affected DJSI (Dow Jones Sustainability Indices) Europe positively. Sayim and Rahman (2015), Yao et al (2017) analyzed that investor sentiment index has a positive relation with the Turkish stock and Shanghai Composite Index, respectively.…”
Section: Gold Price and Stock Market Movement In Various Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exchange rate, forex reserve, current account balance and oil price effect selectively to these sectors. Sariannidis et al (2016) examined the reaction of stock market in Europe due to change in weather condition and found that it has affected DJSI (Dow Jones Sustainability Indices) Europe positively. Sayim and Rahman (2015), Yao et al (2017) analyzed that investor sentiment index has a positive relation with the Turkish stock and Shanghai Composite Index, respectively.…”
Section: Gold Price and Stock Market Movement In Various Countriesmentioning
confidence: 99%
“…A study using environmental variables might be interesting as these variables can affect the stock returns, and it has been recommended by Sariannidis et al (2016). According to Haron and Ayojimi (2019a), the country in which GST is implemented can see the effect, and India did so in 2017.…”
Section: Research Gap Identified In the Indian Context From The Existing Literaturementioning
confidence: 99%
“…The behavioral paradigm, on the other hand, draws on the psychological literature dating back to the 1970s, which demonstrates that the weather affects human behavior 4. More importantly, for our purposes, investor sentiment―and thus financial markets―can be influenced by weather‐related factors such as sunshine and cloud coverage (Bassi et al., 2013; Hirshleifer & Shumway, 2003; Saunders, 1993), wind speed (Keef & Roush, 2002), humidity (Sariannidis et al., 2016), precipitation (Kaustia & Rantapuska, 2016) and air temperature (Bansal & Ochoa, 2011; Cao & Wei, 2005a; Floros, 2011; Keef & Roush, 2007; Peillex et al., 2021; Yan et al., 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The crude oil commodity does have an unfavourable image when investing in the sustainable index [41]. Therefore, an increase in crude oil prices will lead to a decrease in the value of the sustainable index employed [42]. Crude oil volatility will cause shocks to global industries, including in Southeast Asia, which in turn will disrupt the economy [43].…”
Section: Hypothesis Developmentmentioning
confidence: 99%